2014
DOI: 10.1111/bjso.12052
|View full text |Cite
|
Sign up to set email alerts
|

Denunciation and the construction of norms in group conflict: Examples from an Al‐Qaeda‐supporting group

Abstract: In situations of violent group conflict, group members often argue about how to deal with the outgroup. While some argue for aggression, force, and separation, others argue for negotiation and cooperation. Each side attempts to persuade the group that their own position is normative and is most in line with the interests and essence of the group. These arguments often involve denunciations of opponents as disloyal or deviant. In such situations, definitions of group identities and norms, and what counts as loy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…These contrasting diagnoses of the bases for Muslims’ marginalization give rise to contrasting arguments within the community as to how they could and should act to change their predicament. Moreover, such arguments often entail dispute about the nature of Muslim identity (Hopkins & Kahani‐Hopkins, ; Hopkins, Reicher, & Kahani‐Hopkins, ), and in extreme cases, this can take the form of denunciation geared to galvanize support for projects in which the authorities are clearly defined as outgroup (Finlay, ).…”
Section: Discussionmentioning
confidence: 99%
“…These contrasting diagnoses of the bases for Muslims’ marginalization give rise to contrasting arguments within the community as to how they could and should act to change their predicament. Moreover, such arguments often entail dispute about the nature of Muslim identity (Hopkins & Kahani‐Hopkins, ; Hopkins, Reicher, & Kahani‐Hopkins, ), and in extreme cases, this can take the form of denunciation geared to galvanize support for projects in which the authorities are clearly defined as outgroup (Finlay, ).…”
Section: Discussionmentioning
confidence: 99%
“…Broadly defined, these sanctions may include criticism, isolation, social rejection, termination of funding for operations, difficulty in disseminating various types of texts, confiscation of materials, arrests, and even physical harm (e.g., Austin, 2007; Hutt, 2006; Nets-Zehngut, 2011a; Ngok, 2007). More specifically, research from conflict zones such as Turkey (Burris, 2007) and Israel (Finlay, 2005), and with conflict-related groups such as supporters of Al-Qaeda (Finlay, 2014), has shown that individuals who publically disseminate information contradicting an official narrative are perceived by their group members as deviants and labeled as self-hating, traitors, disloyal, mentally weak, ignorant, or even pathological. Consequently, these people become more restrained in their maverick activity to avoid these social sanctions.…”
Section: Self-censorship – Theoretical Backgroundmentioning
confidence: 99%
“…Logic and reasoning are used on both sides of a debate, even when Facebook users display violent, visceral, expressions of hatred. This has been shown to be a common strategy between two groups in conflict, whereby members try to persuade the opposing side that their position is a reasonable one (Finlay, 2014). The use of reasoning has also been found to be a strategy used by politicians to appear as rational when making potentially racist arguments over immigration (e.g.…”
Section: Discussionmentioning
confidence: 99%